"Nobody knows, or seems to know how rheumatology and breastfeeding works": Women's experiences of breastfeeding whilst managing a long-term limiting condition – A qualitative visual methods study. (November 2019) - Williams, Denitza; Webber, Jessica; Pell, Bethan; Grant, Aimee; Sanders, Julia; Choy, Ernest; Edwards, Adrian; Taylor, Ann; Wu, Meng-Chieh; Phillips, Rhiannon
Abstract: Background: Only around 1% of babies in the UK are breastfed exclusively until six months of age as recommended by the World Health Organisation. One in ten women who have recently given birth in the UK have a long-term illness and they are at increased risk of stopping breastfeeding early. We considered women with autoimmune rheumatic diseases as an exemplar group of long term illnesses, to explore the barriers and enablers to breastfeeding Aim: To understand the experiences of infant feeding among women with autoimmune rheumatic diseases and to identify potential barriers and enablers. Design: Qualitative visual timeline-facilitated interviews. Participants and setting: 128 women with autoimmune rheumatic diseases who were considering pregnancy, pregnant, or had young children took part in an online survey as part of the STAR Family Study. Of these, 13 women who had children were purposefully sampled to be interviewed. Interviews took place in person or on the telephone. Timeline-facilitated interviews were used to focus on lived experiences and topics important to the women, including early parenting. We conducted a focused thematic analysis of women's lived experiences of infant feeding. Results: Three main themes were identified in relation to breastfeeding: lack of information about medication safety, lack of support in decision-making and maintaining breastfeeding, and maternal guilt. Conclusions: Women with autoimmune rheumatic diseases found it difficult to access the information they needed about medications to make informed decisions about breastfeeding. They often also felt pressurised into breastfeeding and experienced feelings of guilt if they were unable, or did not wish to breastfeed. Tailored interventions are required that adopt a non-judgmental and person-centred approach to support decision-making in regard to infant feeding, providing women with information that can best enable them to make infant feeding choices.